The Influence of Price Discounts and Online Customer Reviews on Purchasing Decisions in Online Food Delivery Services in Bandar Lampung - Dimaz Satritama Alwan; Dorothy Rouly Haratua Pandjaitan; Nuzul Inas Nabila (International Journal of Economics, Business and Innovation Research, 2026)
The growth of Online Food Delivery (OFD) services in Indonesia, including Gofood, has driven competition, necessitating effective marketing strategies such as price discounts and online customer reviews. This study nalyses the influence of these two variables on food product purchasing decisions through Gofood in Bandar Lampung. The method used is a quantitative approach with a survey of 100 respondents using purposive sampling, as well as multiple linear regression analysis. The results show that price discounts and online customer reviews have a positive and significant effect on purchasing decisions (p-value 0.000 < 0.05). These findings confirm that price discounts and customer reviews are important factors that encourage consumers to make purchases through Gofood in Bandar Lampung.